Pendampingan Optimalisasi Penginputan dan Pembaruan Data Pensiun pada Divisi Sumber Daya Manusia PT Pos Indonesia (Persero) KCU Jakarta Premier - Alsyabina Nursa'bani; Sri Handoko Sakti (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
This activity aims to optimize the pension data input and update process to support human resource administration effectiveness within the Human Resource Division at PT Pos Indonesia (Persero) KCU Jakarta Premier. The partner in this activity faced administrative challenges such as manual processes and repeated verification checks, which potentially affected data accuracy and timeliness. The implementation method used a qualitative descriptive approach through field observations, in-depth interviews with HR staff, and documentation of current workflows. Based on the identification of these issues, the PKM team provided solutions in the form of restructuring work procedures and mentoring the optimization of the internal information system. The results of this activity indicated that restructuring the procedures and strengthening staff capacity in system utilization successfully minimized the bureaucracy of repeated checks, reduced the risk of manual input errors, and accelerated the pension data updating process. Through this assistance, the effectiveness and accuracy of human resource administration management for the partner can be significantly improved.